A survey on oral care practices for ventilator‐assisted patients in intensive care units in 3A hospitals of mainland China. Issue 6 (1st April 2014) - Qu, Xing; Xie, Huixu; Zhang, Qi; Zhou, Xuedong; Shi, Zongdao
Abstract : Oral hygiene is a critical element of patient care, particularly among patients who need ventilator‐assisted equipment. The objective of this study was to explore the current status of oral care practices, attitudes, education and knowledge among intensive care unit (ICU) nurses caring for ventilator‐assisted patients in 3A hospitals in mainland China. To achieve this aim, an 18‐item self‐assessment questionnaire was mailed to head ICU nurses in 189 Grade 3A hospitals. Additional data were collected through in‐person interviews at 38 ICUs throughout Sichuan, Shanxi, Jiangsu provinces, as well as Chongqing and Beijing. We found that most ICUs conducted oral examinations at patient admission, and that this care was largely provided by nurses. The most common oral care methods were foam swabs and mouth rinse containing antibiotics or disinfectants. Although the majority of ICUs provided continuing training for oral care, and most training was conducted by head nurses, the content and scope of training were not consistent among the hospitals in the study. The most popular sources of oral care knowledge were academic journals, Internet and professional books. Overall, it is clear that an evidence‐based oral care standard manual is urgently needed for oral practice in ICUs in mainland China.